Provider perspectives on shared decision-making regarding hypospadias surgery. Issue 3 (June 2020) - Chan, Katherine H.; Misseri, Rosalia; Cain, Mark P.; Whittam, Benjamin; Szymanski, Konrad; Kaefer, Martin; Rink, Richard; Cockrum, Brandon; Moore, Courtney; Wiehe, Sarah
Summary: Introduction: Many parents experience decisional conflict and decisional regret around hypospadias surgery. The utilization of a shared decision-making (SDM) process may mitigate these issues, however addressing the principal components of the SDM process is a complex task that requires the investment of providers. Objective: The purpose of this study was to facilitate a discussion about SDM anchored on hypospadias with pediatric urology and general pediatric providers to explore perspectives, clinical applications and barriers to adopting SDM in clinical practice. Study design: We conducted two focus groups in order to engage pediatric urology and general pediatric providers in guided discussions about SDM anchored on hypospadias . All activities were audio recorded and professionally transcribed. The transcripts were analyzed by three coders using directed qualitative content analysis techniques to identify themes and relationships between themes to inform the development of an affinity diagram (Extended Summary Figure). Results: Two focus groups were held; one with seven pediatric urology providers in November 2018 and one with ten general pediatric providers in January 2019 (median age 51 years, 88.2% Caucasian, 58.8% female, 70.6% physicians and 29.4% nurse practitioners). Both groups identified some of the key components of SDM including engaging families in decision-making, informing them about treatment options and clarifying values/preferences (Extended Summary Figure). They thought that SDM was useful for discussing preference-sensitive conditions (e.g. hypospadias) and addressing parental compliance. General pediatric providers also suggested that SDM helped them avoid unnecessary referrals to specialists. Both groups identified parental, provider and systemic barriers to the adoption of SDM: a) desire for paternalism, b) misperceptions about medical evidence, c) completion of parental decision-making prior to the clinical visit, d) provider bias/lack of interest and e) time constraints/productivity pressures. Discussion: Providers who care for hypospadias patients are knowledgeable about SDM and its potential clinical applications. They identified several potentially modifiable barriers to the adoption of a SDM process about hypospadias surgery in a pediatric clinical setting. Conclusions: Based on feedback from providers, we plan to implement a hypospadias decision aid early in the parental decision-making process about hypospadias such as in the postpartum unit and at well-child visits in the newborn period and provide a provider training session about SDM to address the identified knowledge gaps. Summary Figure Affinity map of provider perspectives on shared decision-making: components, applications and barriers. Red = pediatric urology providers. Blue = general pediatric providers. Purple = both groups. Extended Summary Figure